The Presence of Mef (E) and Erm (B) Genes in Throat Samples of Children Infected with Streptococcus pyogenes - Çiğdem Eda Balkan Bozlak; Ahmet Yılmaz; Hayrunnisa Bekis Bozkurt; Cem Öziç (Journal of Contemporary Medicine, 2021)
Aim: Antibiotic resistance studies about the Streptococcus have a great importance for the treatment of especially child throat infections in terms of public health and rational antibiotic use. For this purpose, we aimed to identify the macrolide resistance genes mef(E) and erm(B). Material and Method: The throat culture samples taken from 51 children presenting to the hospital with the complaint of sore throat were evaluated in the laboratory, and S. pyogenes was diagnosed using tests; gram staining, catalase, bacitracin and PYR. Susceptibility profile was determined with the Kirby-Bauer disk-diffusion method and minimum inhibitor concentration(MICs) of erythromycin and clindamycin was determined by VITEK 2 System. Results: S. pyogenes was possible macrolide resistance genes of mef(E) and erm(B) was determined by PCR. Macrolide resistance in S. pyogenes are determined in 51 pateients as follows; benzylpenicillin 0%, erytromycin 74.5%, clindamycin 31.4%. In patients with S. pyogenes, the genetic determinants of macrolide resistance mef(E) and erm(B) genes was investigated with the PCR method using primers specific to each gene. Total of 48% of the isolates (n=24) were positive for erm (B), 10% (n=5) for mef(E), in 42% (n=21) of the isolates both genes were detected. Conclusion: The results of our study show that macrolid resistance genes were found in five of the patients evaluated. When the anamnesis of these patients was examined, it was determined that there were patients that frequently presented to the hospital with throat infections and experienced re-infection within a few weeks after receiving treatment.